Using Microsoft Windows Small Business Server 2003 - Hassell, Jonathan (Apress : Imprint: Apress, 2005)
This is the fundamental, definitive reference to Microsoft Small Business Server 2003. And it is relevant for all audiences: for beginners just embracing the notion of computerizing their small businesses, to IT consultants specializing in SBS implementation and deployment. The book focuses on pragmatic solutions, not drawn-out theoretical discussions. And author Jonathan Hassell is a recognized authority on Windows network administration, who smartly approaches the product objectively, without evangelizing. The chapters will steer you through installation, configuration, exploration, and support.